Voices from the past: Comparing the rapid prompting method and facilitated communication. (August 2014) - Tostanoski, Amy; Lang, Russell; Raulston, Tracy; Carnett, Amarie; Davis, Tonya
<x xml:space="preserve">Abstract</x> Objective: This article briefly reviews the history and damage caused by facilitated communication (FC) and highlights the parallels between FC and the Rapid Prompting Method (RPM). Background: FC involves a therapist (or facilitator) supporting the hand of a person with autism while a message is typed on a letter board. FC is widely acknowledged to be a pseudoscientific, unsafe, and unethical treatment for people with autism. RPM is a more recent intervention for people with autism that involves the facilitator holding and moving the letter board while the individual with autism moves their own hand. Those who espouse the perceived benefits of FC and RPM make strikingly similar claims of hidden intelligence and extraordinary communication abilities in people with autism following treatment. Conclusion: Clients, proponents, and practitioners of RPM should demand scientific validation of RPM in order to ensure the safety of people with disabilities that are involved with RPM.